Деякі питання щодо вдосконалення окремих криміналістичних методик - Малярова, В. О.; Maliarova, V. O.; ORCID: http://orcid.org/0000-0002-0766-0752; Андрєєв, О. О.; Andrieiev, O. O. (Форум права. - 2017. - № 5. - С. 247–251, 2017)
Досліджено деякі актуальні питання, щодо окремих криміналістичних методик, з огляду на взаємозв’язок розслідування злочинів як кримінально-процесуального інституту і методики розслідування злочинів як криміналістичної категорії. Запропоноване авторське поняття методичних рекомендацій, як цілеспрямовано створеної, науково обґрунтованої, узагальненої і упорядкованої сукупності криміналістичних, процесуальних, організаційних та інших засобів, застосованих з метою ефективного розслідування злочину та своєчасного викриття особи, яка його вчинила.

The article discusses some topical issues of private criminalistics methods, taking into account the relationship of the criminal investigation process, as a criminal procedure institute and methods of investigating a particular type of crime, as a criminalistics category. The authors proposed the definition of methodological recommendations as a purposefully created, scientifically grounded, generalized and ordered set of forensic, procedural, organizational and other means used to effectively investigate a crime and timely expose the person who committed it. Purposeful application of a separate forensic technique requires its adaptation to the specific circumstances of the investigation, which are determined in the first place by a range of circumstances that arise in the investigation of crimes. The nature of the circumstances affects what investigative (search) actions or complexes of investigators (investigators) and unscrupulous investigators (investigators) can obtain evidence. This necessitates the consideration of the characteristics of typical investigative situations that arise in the investigation of crimes of the relevant species when developing certain criminalistic methods. It is shown that the basis of the establishment of methods for investigating crimes is: a) forensic classification of a specific type of crime; b) the content of their typical forensic characteristics; c) the nature of the typical investigative situations of the initial stage of the investigation; d) the list and scope of the tasks of the initial stage of the investigation, as well as the description of the means of their implementation. Compliance with these conditions ensures individuality, concreteness, completeness, constructiveness and orientation of the content of the methodology for investigating a particular type of crime.

Исследованы некоторые актуальные вопросы частных криминалистических методик, с учетом взаимосвязи процесса расследования преступления, как уголовно-процессуального института и методик расследования отдельного вида преступлений, как криминалистической категории. Авторами предложено определение методических рекомендаций, как целенаправленно созданной, научно обоснованной, обобщенной и упорядоченной совокупности криминалистических, процессуальных, организационных и других средств, применяемых для эффективного расследования преступления и своевременного разоблачения лица, его совершившего.
Some Questions of Perfection of Separate Criminalistic Techniques
Некоторые вопросы совершенствования отдельных криминалистических методик
Малярова В. О. Деякі питання щодо вдосконалення окремих криміналістичних методик [Електронний ресурс] / В. О. Малярова, О. О. Андрєєв // Форум права. - 2017. - № 5. - С. 247–251. – Режим доступу: http://nbuv.gov.ua/j-pdf/FP_index.htm_2017_5_39.pdf.
Малярова В. О., Андрєєв О. О. Деякі питання щодо вдосконалення окремих криміналістичних методик. Форум права: електрон. наук. фахове вид. 2017. № 5. С. 247–251. URL: http://nbuv.gov.ua/j-pdf/FP_index.htm_2017_5_39.pdf.
Малярова В. О., Андрєєв О. О. "Деякі питання щодо вдосконалення окремих криміналістичних методик." Форум права 5 (2017): 247–251.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; розслідування злочинів; доказування; методики розслідування окремих видів злочинів; методичні рекомендації; расследование преступлений; доказывание; методики расследования отдельных видов преступлений; методические рекомендации; investigation of crimes; proof; methods of investigation of certain types of crimes; methodical recommendations; розслідування окремих видів злочинів; investigation of certain types of crimes; расследование отдельных видов преступлений